2006
DOI: 10.1016/j.febslet.2006.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Novel potential of tunicamycin as an activator of the aryl hydrocarbon receptor – dioxin responsive element signaling pathway

Abstract: Tunicamycin is a well-known inhibitor of protein glycosylation and used as an inducer of endoplasmic reticulum (ER) stress. We found that tunicamycin induced expression of cytochrome P450 1A1 in a dose-dependent manner. Like dioxin, the transcriptional induction was associated with dose-dependent activation of the dioxin responsive element (DRE). This effect was independent of inhibition of protein glycosylation or induction of ER stress. Pharmacological and genetic inhibition of the aryl hydrocarbon receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…(56) It is also possible that the ER stress response during colitis facilitates AhR signaling and their reciprocal induction leads to the inflammatory response associated with DSS induced colitis. (57)…”
Section: Discussionmentioning
confidence: 99%
“…(56) It is also possible that the ER stress response during colitis facilitates AhR signaling and their reciprocal induction leads to the inflammatory response associated with DSS induced colitis. (57)…”
Section: Discussionmentioning
confidence: 99%
“…Exposure groups were prepared in HBSS buffer (LuBioScience, Lucerne, Switzerland), and a solvent concentration of 0.5% DMSO (Sigma Aldrich, Buchs, Switzerland). Tunicyamycin (Enzo Lifescience, Lausen, Switzerland) is a known ER stress inducer and was furthermore found to induce CYP1A [ 27 ]. Afterwards, the liver was fixed in RNA Later (Qiagen, Basel, Switzerland), RNA was extracted, cDNA synthesized, and qRT-PCR performed (see Section 5.9).…”
Section: Methodsmentioning
confidence: 99%
“…Our results may indicate that the observed effect of inhibition of CSFV propagation by low doses of tunicamycin may be caused by some other mechanisms than N-glycosylation inhibition. It has been reported that low doses of tunicamycin affect cellular receptors and signal transduction (Mauro et al, 2003;Horikawa et al, 2006) and these effects may inhibit proper transport of viral components and virus maturation.…”
Section: In Situ Analysis Of Localization Of Csfv Glycoproteins In Skmentioning
confidence: 99%